SPIG2018 - Obradovi?, Bratislav (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue covers a wide range of topics from fundamental studies to applications of ionized gases. It is dedicated to four topics of interest: 1. ATOMIC COLLISION PROCESSES (electron and photon interactions with atomic particles, heavy particle collisions, swarms, and transport phenomena); 2. PARTICLE AND LASER BEAM INTERACTION WITH SOLIDS (atomic collisions in solids, sputtering and deposition, and laser and plasma interactions with surfaces); 3. LOW TEMPERATURE PLASMAS (plasma spectroscopy and other diagnostic methods, gas discharges, and plasma applications and devices); 4. GENERAL PLASMAS (fusion plasmas, astrophysical plasmas, and collective phenomena). This Special Issue of Atoms will highlight the need for continued research on ionized gas physics in different topics ranging from fundamental studies to applications, and will review current investigations.